Mechanics of bar straightening, Part 2: Straightening in cross-roll straighteners - Das Talukder N.K.; Singh A.N. (My University, 2025)
An analysis is made of the straightening process of rolled circular bars and tubes, with initial residual curvature in different types of cross-roll straighteners indicating the degree of straightness and throughput speed obtainable from them. Suggestions are made for roll arrangement for higher throughput speed and degree of straightness of the product. © 1991 by ASME.